PEMBELAJARAN PENDIDIKAN ISLAM DI PESANTREN TAHFIZH DAARUL QUR’AN SELAMA MASA PANDEMI COVID-19 - Fathulloh, Moh. Kholis (Institut Daarul Qur'an Jakarta, Indonesia, 2021)
Corona Virus is a new type of virus that is infectious to the human body. Covid 19 was first discovered in the end of December 2019 in Wuhan, Hubei Province, China. The spread of covid 19 in Indonesia was known at the beginning of march 2020. Beside the increase of Covid 19 in Indonesia, the virus has an indirect impact for Indonesia. In addition, this virus changes a lot of people's lives, especially in society. One of the impacts of covid 19 in education sectors, which is the Learning process of Islamic Education. Islamic boarding school is an institution that focuses on the science of religion, such as the Qur'an, the Hadith, Arabic language, as well as the science of the shari'ah and others. Pesantren Tahfizh Daarul Qur'an is an institution founded by Ust. Yusuf Mansur. It is located in the Kampung Qur'an, Cipondoh, Tangerang, an area built by the PPPA Daarul qur'an. This journal aims to determine and deepen the profile as well as the implementation of learning Islamic education in Pesantren Tahfidz Daarul Qur'an during the pandemic of covid 19. The method used in this study is library research. In this case, the reference is derived from writings, books, and online sites. The results of this study indicate that Islamic education learning must be carried out under any circumstances and accomplished with any conditions.